Current management of spontaneous intracerebral haemorrhage. Issue 1 (24th January 2017) - Dastur, Cyrus K; Yu, Wengui
Abstract : Intracerebral haemorrhage (ICH) is the most devastating and disabling type of stroke. Uncontrolled hypertension (HTN) is the most common cause of spontaneous ICH. Recent advances in neuroimaging, organised stroke care, dedicated Neuro-ICUs, medical and surgical management have improved the management of ICH. Early airway protection, control of malignant HTN, urgent reversal of coagulopathy and surgical intervention may increase the chance of survival for patients with severe ICH. Intensive lowering of systolic blood pressure to <140 mm Hg is proven safe by two recent randomised trials. Transfusion of platelets in patients on antiplatelet therapy is not indicated unless the patient is scheduled for surgical evacuation of haematoma. In patients with small haematoma without significant mass effect, there is no indication for routine use of mannitol or hypertonic saline (HTS). However, for patients with large ICH (volume > 30 cbic centmetre) or symptomatic perihaematoma oedema, it may be beneficial to keep serum sodium level at 140–150 mEq/L for 7–10 days to minimise oedema expansion and mass effect. Mannitol and HTS can be used emergently for worsening cerebral oedema, elevated intracranial pressure (ICP) or pending herniation. HTS should be administered via central line as continuous infusion (3%) or bolus (23.4%). Ventriculostomy is indicated for patients with severe intraventricular haemorrhage, hydrocephalus or elevated ICP. Patients with large cerebellar or temporal ICH may benefit from emergent haematoma evacuation. It is important to start intermittent pneumatic compression devices at the time of admission and subcutaneous unfractionated heparin in stable patients within 48 hours of admission for prophylaxis of venous thromboembolism. There is no benefit for seizure prophylaxis or aggressive management of fever or hyperglycaemia. Early aggressive comprehensive care may improve survival and functional recovery.